2018
DOI: 10.3892/ol.2018.8903
|View full text |Cite
|
Sign up to set email alerts
|

FGF2 and FGFR2 in patients with idiopathic pulmonary fibrosis and lung cancer

Abstract: The aim of this study was to investigate the expression of FGF2 and FGFR2 in patients with idiopathic pulmonary fibrosis (IPF) and lung cancer (LC) as well as their clinical significance. Reverse transcription-quantitative PCR (RT-qPCR) and western blotting were used to detect FGF2 and FGFR2 expression in LC and adjacent normal tissues of LC patients and lavage fluid of idiopathic pulmonary fibers patients and normal controls (confirmed by bronchoalveolar lavage examination). The expression levels of FGF2 mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Human lavage fluid was collected from 10 IPF patients and 9 normal controls in Shanghai Pulmonary Hospital as previously reported (Li et al, 2018). This study was approved by the Medical Ethics Committee of Shanghai Pulmonary Hospital (Shanghai, China), and all patients were informed and signed informed consent.…”
Section: Contact For Reagent and Resource Sharingmentioning
confidence: 99%
“…Human lavage fluid was collected from 10 IPF patients and 9 normal controls in Shanghai Pulmonary Hospital as previously reported (Li et al, 2018). This study was approved by the Medical Ethics Committee of Shanghai Pulmonary Hospital (Shanghai, China), and all patients were informed and signed informed consent.…”
Section: Contact For Reagent and Resource Sharingmentioning
confidence: 99%
“…These data were used to study the relationship between 15 genes and TME among patients with high versus low immune scores or stromal score groups using the ESTIMATE algorithm. Previous studies have reported that 9 out of the 15 immune genes associated with prognosis (S100A16, CRABP1, RBP2, FGF2, FPR2, BDNF, ANGPTL4, SEMA4B and VIPR1 [33][34][35][36][37][38][39][40][41]) are involved in the pathogenesis of lung cancer. The remaining six genes (IGKV4-1, IGKV6D-41, TNFRSF11A, INHA, IL11 and SCH3) have not been reported in the literature and may be used as potential biomarkers for lung cancer research.…”
Section: Discussionmentioning
confidence: 99%
“…As another example, IH downregulated fibroblast growth factor receptor (FGFR-2) in alveolar type 2 cells. FGFR2 promotes alveolar regeneration in response to lung injury (56), and is upregulated in patients with idiopathic pulmonary fibrosis (57). Previous studies suggest that OSA can induce injury to the lung (58,59), and OSA is prevalent in patients with idiopathic pulmonary fibrosis (36).…”
Section: Discussionmentioning
confidence: 99%